Kinetic Study and Simulation of Oleic Acid Esterification in Different Type of Reactors - S. Abbas, Ammar; M. Abbas, Sura (Iraqi Journal of Chemical and Petroleum Engineering, 2013)
Esterification reaction is most important reaction in biodiesel production. In this study, oleic acid was used as a suggested feedstock to study and simulate production of biodiesel. Batch esterification of oleic acid was carried out at operating conditions; temperature from 40 to 70 °C, ethanol to oleic acid molar ratio from 1/1 to 6/1, H2SO4 as the catalyst 1 and 5% wt of oleic acid, reaction time up to 180 min. The optimum conditions for the esterification reaction were molar ratio of ethanol/oleic acid 6/1, 5%wt H2SO4 relative to oleic acid, 70 °C, 90 min and conversion of oleic 0.92. The activation energy for the suggested model was 26625 J/mole for forward reaction and 42189 J/mole for equilibrium constant. The obtained results simulated to other types of reactors with different operating conditions using reactop cascade package. The conversion of oleic acid of simulation results at optimum operating conditions was 0.97 for isothermal batch and plug flow reactors, 0.67 for isothermal CSTR, while the conversions of oleic acid in the adiabatic mode were 0.82, 0.40, 0.74 for batch, CSTR, PFR reactors respectively.